2020 takeaways: A conversation with enrollment marketers. Issue 5 (27th January 2021) - Talarico, Donna
Abstract : The start of a new year is a good time for reflection. While the past 12 months brought stress and change our way — personally and professionally — powering through the marketing challenges of 2020 has also presented lessons.